Effectiveness of the Use of Facilities and Infrastructure at the Takalar Regency Education and Culture Office - Saputri, Arnita; Saleh, Sirajuddin; Nasir, Nasir; Tenriyola, Andi Putri (Pinisi Journal of Officers Review, 2025)
The effectiveness of using facilities and infrastructure at the Takalar Regency Education and Culture Office plays a vital role in improving the quality of education. Properly managed facilities that are efficient, flexible, and user-oriented support both administrative processes and teaching activities. Yet, challenges remain, including uneven distribution of facilities, limited maintenance, and underutilized technology. This study aims to analyze the effectiveness of facility and infrastructure use within the Takalar Regency Education and Culture Office and to identify supporting and inhibiting factors. A qualitative approach was applied through observation, interviews, and documentation. The findings reveal that from an efficiency standpoint, the use of facilities and infrastructure is not yet optimal. Several employees still lack adequate equipment to perform their duties effectively. In terms of flexibility, the available facilities are sufficient to accommodate various administrative tasks, offering ease of use and contributing to smoother office operations. Regarding employee satisfaction, most respondents expressed that the facilities significantly support their performance and boost motivation at work. From the development aspect, there has been improvement in both quality and quantity, aligning with the institution’s functional needs. The study also identifies government support through budget allocation, policy direction, and resource provision, as a key supporting factor. Conversely, limitations in facilities, budget constraints, and weak supervision in facility management are major obstacles. Overall, comprehensive planning and stronger management strategies are needed to optimize facility utilization and ensure these resources effectively enhance the quality of education in Takalar Regency.